2010
DOI: 10.1111/j.1365-2125.2010.03647.x
|View full text |Cite
|
Sign up to set email alerts
|

An open‐label, single‐dose bioavailability study of the pharmacokinetics of CAT‐354 after subcutaneous and intravenous administration in healthy males

Abstract: WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT• The safety profile and effective dose of CAT-354 have been determined with intravenous (i.v.) administration, but no information is available on subcutaneous (s.c.) administration. WHAT THIS STUDY ADDS• This study characterized the pharmacokinetics of CAT-354 following s.c. administration of 150 mg and 300 mg doses, and indicated a bioavailability of approximately 60%. AIMTo assess the bioavailability and pharmacokinetics of CAT-354, an anti-IL-13 human monoclonal IgG4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
44
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 22 publications
7
44
0
Order By: Relevance
“…Following SC administration, the reported bioavailability of mAbs and Fc fusion proteins in humans are: adalimumab, 64%; canakinumab, 63-67%; certolizumab pegol, 76-88%; efalizumab, 50%; etanercept, 76%; golimumab, 53%; omalizumab, 53-71%; rilonacept, 43%; ustekinumab, 57% (2,63), and CAT-354 an anti-IL-13 human monoclonal IgG4 antibody 60-62% (64). Systemic bioavailability data of mAbs in various species are listed in Table II.…”
Section: Bioavailability Following Sc Injectionmentioning
confidence: 99%
“…Following SC administration, the reported bioavailability of mAbs and Fc fusion proteins in humans are: adalimumab, 64%; canakinumab, 63-67%; certolizumab pegol, 76-88%; efalizumab, 50%; etanercept, 76%; golimumab, 53%; omalizumab, 53-71%; rilonacept, 43%; ustekinumab, 57% (2,63), and CAT-354 an anti-IL-13 human monoclonal IgG4 antibody 60-62% (64). Systemic bioavailability data of mAbs in various species are listed in Table II.…”
Section: Bioavailability Following Sc Injectionmentioning
confidence: 99%
“…In this study, we further explored IL-13-directed mechanisms in pulmonary fibrosis via the use of tralokinumab, an investigational human IgG4 monoclonal antibody that selectively neutralizes human IL-13 (27)(28)(29). We observed that the IL-13 pathway was significantly enhanced in biopsy samples from patients who exhibited a rapidly progressing form of IPF compared with patients with IPF with a slower rate of lung function loss (30), and inhibition of human IL-13 with tralokinumab attenuated established pulmonary fibrosis in a humanized SCID mouse model of IPF, notably with a reduction in lung epithelial cell damage.…”
mentioning
confidence: 99%
“…The selected maximum dose (10.0 mg/kg, IV) for FIH study of CNTO 5825 provided predicted systemic exposures that were below observed systemic exposures at NO-AEL in rats and cynomolgus monkeys. In addition, the selected doses (0.1, 0.3, 1.0, 3.0 and 10.0 mg/kg) of CNTO 5825 for FIH study were within the range of doses that have been evaluated in clinical studies of related anti-IL-13 mAbs [33][34][35][36].…”
Section: Discussionmentioning
confidence: 94%